Deletion of human GP1BB and SEPT5 is associated with Bernard-Soulier syndrome, platelet secretion defect, polymicrogyria, and developmental delay - Bartsch, Ingrid; Sandrock, Kirstin; Lanza, Francois; Nurden, Paquita; Hainmann, Ina; Pavlova, Anna; Greinacher, Andreas; Tacke, Uta; Barth, Michael; Busse, Anja; Oldenburg, Johannes; Bommer, Martin; Strahm, Brigitte; Superti-Furga, Andrea; Zieger, Barbara (Thrombosis and Haemostasis, 2011)
The bleeding disorder Bernard-Soulier syndrome (BSS) is caused by mutations in the genes coding for the platelet glycoprotein GPIb/IX receptor. The septin SEPT5 is important for active membrane movement such as vesicle trafficking and exocytosis in non-dividing cells (i.e. platelets, neurons). We report on a four-year-old boy with a homozygous deletion comprising not only glycoprotein Ibβ (GP1BB) but also the SEPT5 gene, located 5’ to GP1BB. He presented with BSS, cortical dysplasia (polymicrogyria), developmental delay, and platelet secretion defect. The homozygous deletion of GP1BB and SEPT5, which had been identified by PCR analyses, was confirmed by Southern analyses and denaturing HPLC (DHPLC). The parents were heterozygous for this deletion. Absence of GPIbβ and SEPT5 proteins in the patient’s platelets was illustrated using transmission electron microscopy. Besides decreased GPIb/IX expression, flow cytometry analyses revealedimpaired platelet granule secretion. Because the bleeding disorder was extremely severe, the boy received bone marrow transplantation (BMT) from a HLA-identical unrelated donor. After successful engraftment of BMT, he had no more bleedingepisodes. Interestingly, also his mental development improved strikingly after BMT. This report describes for the first time a patient with SEPT5 deficiency presenting with cortical dysplasia (polymicrogyria), developmental delay, and platelet secretion defect.
Keywords: Inherited / acquired platelet disorders; paediatric haemostasis; platelet glycoproteins; platelet pathology / inherited; aquired